Making Crusades. The importance of crusades for Europe (Zien Journal of Social Sciences and Humanities, 2022)
The reasons for the crusades in which the crusades participated in these marches, leaders, managers of the crusades, were highlighted by issues such as the importance of managers, cruscriptions, the importance of crusades for Europe